Shifting Rights to Education of Adopted Children in Terantang Village Perspective of Islamic Law - Agustar, Armi; Mutasir (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
Providing the right to proper education for adopted children is the basic goal of adoption. The right to education is one of the rights that must be fulfilled by adoptive parents. In general, the organizers of children's rights above are the obligation and responsibility of the government and society. This research states that in Islamic law adopting a child is a good deed, which helps adopted children get a proper education. The phenomenon that occurred in Trantang Village, the right to education for adopted children shifted to utilization, because it was caused by several factors, one of which was from an economic perspective. The purpose of this research is to strengthen previous research, and to further examine the shift in educational rights for adopted children and to look at the factors that lead to non-fulfillment of adoption rights in Trantang Village. This study uses a sociological normative. The results of this study found several factors that resulted in a shift in educational rights, even the rights of adopted children were not given, such as: economic factors, community habits and social media factors. In fact, in Islam, adoption is a good deed, but over time this right shifts to utilization.